Using active learning methodologies in physical chemistry in CLIL contexts - David Recatalá (Multidisciplinary Journal for Education, Social and Technological Sciences)
One of the main objectives of the European Higher Education Area (EHEA) is to promote a change toward a student-centred education model. This fact has led to the implementation of novel methodologies based on active learning, aimed at engaging students’ interest. This implementation has been usually accompanied by significant changes in both the teaching and learning processes in European universities. Furthermore, teaching a subject through the medium of a foreign language has also been gaining attention over the past few years. More specifically, this approach commonly known as Content and Language Integrated Learning (CLIL) has been employed for the simultaneous learning of content and English in a number of European countries. In this contribution we report on the active learning methods implemented in a Physical Chemistry course, as well as the efforts devoted to Content and English Language Integration in this subject. This research analyses a series of factors that can contribute to the global learning and teaching experience when both active learning and CLIL are implemented in the Physical Chemistry classroom. Some examples of them include changes in attitudes towards the subject, engagement and motivation during the course, perception of English learning, and in general, students’ satisfaction with the learning process.